The Essence, Types and Effects of Foreign Language Control Systems - Szczodrowski, Marian (Glottodidactica, 2009)
Every human activity, including linguistic and non-linguistic communication among people, is always connected with a type of control appropriate to that activity. In an informationalcommunicative system there functions a parallel control system, which ensures the optimum transfer of information to the receiver or receivers. The following article deals with the essence of the process of control, its course on the inter-individual and intra-individual level of communication between partners, and types of control and their possible effects.